Prenatal exposure to persistent organic pollutants in association with offspring neuropsychological development at 4 years of age: The Rhea mother-child cohort, Crete, Greece. (December 2016) - Kyriklaki, Andriani; Vafeiadi, Marina; Kampouri, Mariza; Koutra, Katerina; Roumeliotaki, Theano; Chalkiadaki, Georgia; Anousaki, Despoina; Rantakokko, Panu; Kiviranta, Hannu; Fthenou, Eleni; Bitsios, Panos; Kyrtopoulos, Soterios A.; et al.
Abstract: Background: Persistent Organic Pollutants (POPs) are highly-resistant compounds to environmental degradation and due to fat solubility they bioaccumulate through the food chain. As they cross the placenta, in utero exposure to POPs could disrupt child neurodevelopment as they are considered to be neurotoxic. Aims: We examined whether in utero exposure to levels of different POPs is associated with offspring cognitive and behavioral outcomes at 4 years of age in a mother-child cohort in Crete, Greece (Rhea study). Methods: We included 689 mother-child pairs. Concentrations of several polychlorinated biphenyls (PCBs) and other organochlorine compounds (dichlorodiphenyl dichloroethene [DDE], hexachlorobenzene [HCB]) were determined in maternal serum collected in the first trimester of pregnancy by triple quadrupole mass spectrometry. Neurodevelopment at 4 years was assessed by means of the McCarthy Scales of Children's Abilities. Behavioral difficulties were assessed by Strengths and Difficulties Questionnaire and Attention Deficit Hyperactivity Disorder Test. Linear regression analyses were used to estimate the associations between the exposures and outcomes of interest after adjustment for potential confounders. Results: Children with "high" HCB concentrations (≥ 90th percentile) in maternal serum, demonstrated decreased scores in perceptual performance (adjusted β = − 6.07; 95% CI: − 10.17, − 1.97), general cognitive (adjusted β = − 4.97; 95% CI: − 8.99, − 0.96), executive function (adjusted β = − 6.24; 95% CI: − 10.36, − 2.11) and working memory (adjusted β = − 4.71; 95% CI: − 9.05, − 0.36) scales at 4 years of age. High exposure to PCBs (≥ 90th percentile) during pregnancy was associated with a 4.62 points reduction in working memory score at 4 years of age (95% CI: − 9.10, − 0.14). Prenatal exposure to DDE, HCB and PCBs was not associated with child behavioral difficulties. Conclusions: The findings suggest that prenatal exposure to HCB and PCBs may contribute to reduced cognitive development at preschool age. Our results raise the possibility that exposure to HCB may play a more important role in child cognition than previously considered. Highlights: We explored effects of in utero exposure to POPs on cognition & behavior at 4 years. Inverse associations of HCB concentration with neurodevelopmental scores were found. High exposure to PCBs during pregnancy was linked to decreased working memory. Prenatal exposure to POPs was not associated with child behavioral difficulties. In utero exposure to HCB may play an important role in child neurodevelopment.